Translanguaging in Academic Writing Classroom: A Case Study of EFL Pre-Service Teachers's Perception - Yolanda, Ika Yasyinta Nindy; Setyaningsih, Endang; Drajati, Nur Arifah (JEELS (Journal of English Education and Linguistics Studies), 2024)
This case study explores the perceptions of translanguaging in the academic writing process of pre-service teachers. Drawing upon the theories of forms translanguaging (Baynham & Lee, 2019; Garcia & Lin, 2016; Hua & Wei, 2022) and the stages of writing proposed by Hyland (2003), this research delves into how pre-service teachers perceive and utilize translanguaging in their writing. The study integrates observations, interviews, and artifact analysis involving pre-service teachers to understand their engagement with translanguaging as both a communicative and pedagogical strategy. The findings show that pre-service teachers not only view translanguaging as a method for effective communication but also as a crucial tool for enhancing their engagement with academic content, particularly in the stages of topic selection, pre-writing, writing, and feedback. In addition, the significant use of translation, code-mixing, and code-switching underscores their linguistic adaptability in a multilingual academic context. This research contributes to the academic discourse by providing insights into the role of translanguaging in the academic writing process and its implications for future teaching practices.